Innovative processing approaches for producing chemical-free jaggery from sugarcane - Mann, Sandeep; Kaur, Navjot; Sharma, Rajiv; Balakrishnan, Renu; Simran (Indian Farming, 2025)
Jaggery production from sugarcane is vital for rural employment and value addition, yet conventional methods rely on chemical clarificants that compromise quality and safety. Under the ICAR-CIPHET’s Farmer FIRST Programme, an improved, chemical-free, and energy-efficient jaggery-making system was introduced at Uppal Farm, Rahon (SBS Nagar). Using plant-based clarificants like okra mucilage and a multi-pan furnace burning sugarcane waste, the process enhances energy efficiency and product purity. The improved system enables production of both solid and granular jaggery, offering a sustainable, health-safe, and income-generating alternative for farmers.